2010
DOI: 10.1590/s1806-83242010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone ingrowth into porous titanium implant: histomorphometric analysis in rabbits

Abstract: A porous material for bone ingrowth with adequate pore structure and appropriate mechanical properties has long been sought as the ideal bone-implant interface. This study aimed to assess in vivo the influence of three types of porous titanium implant on the new bone ingrowth. The implants were produced by means of a powder metallurgy technique with different porosities and pore sizes: Group 1 = 30% and 180 µm; Group 2 = 30% and 300 µm; and Group 3 = 40% and 180 µm. Six rabbits received one implant of each typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 25 publications
1
49
1
1
Order By: Relevance
“…The porous and rough surface of the implant ensures stronger adhesion between an implant and a bone tissue by promoting the biomechanical connection [50]. Many studies have shown that implants with a pore diameter between 100 and 400 µm are best for bone implants, because such pore diameters facilitate cell penetration, tissue ingrowth, vascularization and transport of nutrients to healing tissues [51][52][53]. Fortunately, both SLM and EBM machines enable the production of complex three-dimensional titanium structures with controlled porosity.…”
Section: Titanium Alloys In the Biomedical Fieldmentioning
confidence: 99%
“…The porous and rough surface of the implant ensures stronger adhesion between an implant and a bone tissue by promoting the biomechanical connection [50]. Many studies have shown that implants with a pore diameter between 100 and 400 µm are best for bone implants, because such pore diameters facilitate cell penetration, tissue ingrowth, vascularization and transport of nutrients to healing tissues [51][52][53]. Fortunately, both SLM and EBM machines enable the production of complex three-dimensional titanium structures with controlled porosity.…”
Section: Titanium Alloys In the Biomedical Fieldmentioning
confidence: 99%
“…Materials produced by these methods present an interface between the dense core and porous coating [8,[60][61][62][63]. To overcome this problem a new method to produce titanium samples was to develop, that exhibit a dense core with an integrated porous surface, reducing the problems of displacing a porous coating [6,7,64].…”
Section: Dense Core Implants With An Integrated Porous Surfacementioning
confidence: 99%
“…Currently, implant dentistry focuses on studies that address and enable more rapid osseointegration of implants for orthopedic and dental use, in an attempt to reduce or even eliminate the period of bone healing free from functional load [2]. Among the various lines of research oriented toward this purpose, the topographical characteristics of the implant surface at the bone-implant interface are considered relevant due to the strong influence on the quality of osseointegration achieved [3][4][5][6][7][8], together with the characteristics of the biomaterial from which the implant is produced [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations